If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 = 9x + -5 Reorder the terms: -3 + 5x = 9x + -5 Reorder the terms: -3 + 5x = -5 + 9x Solving -3 + 5x = -5 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -3 + 5x + -9x = -5 + 9x + -9x Combine like terms: 5x + -9x = -4x -3 + -4x = -5 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + -4x = -5 + 0 -3 + -4x = -5 Add '3' to each side of the equation. -3 + 3 + -4x = -5 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = -5 + 3 -4x = -5 + 3 Combine like terms: -5 + 3 = -2 -4x = -2 Divide each side by '-4'. x = 0.5 Simplifying x = 0.5
| 4(x+1.53)=3x | | 600x-0.12=400x+0.58 | | 2.2x-16=1.4x+4 | | 5.5=3x+7.6 | | 1.8125= | | -4x^2+20x+8=0 | | 3/16+1/2-3/16+3/2-3/16= | | 5.1x+3-1.1x=7 | | (6x+2)+4=28 | | (3*x)*(x-8)*(x-8)=135 | | 7y-6=-14+3y | | 8x-62.3=x | | 6x+7x-2x-5=28 | | 5+(-22)+6+(-9)= | | 42=8x+10 | | 8r+5=17 | | q-p-1.5p= | | 20x+7=5x+10whatisx | | 6y-14=20+3y | | 35=7n | | z-6=29 | | 5(x-1)+3=2(2x+4) | | (16x^2)+(9y^2)+(64*x)+(90*y)=287 | | 154/22= | | 5x-2(3+2x)=1 | | 9x+8x-7x-5=45 | | 2r+6=8 | | 9(x-2)=4(2x-3) | | 3(x-4)-5=2x-9 | | 7(x-2)=6 | | 3x^4+4x^3-2=0 | | 4x+7y+6x+9y= |